Tafsir Ayat Tentang Iman Kepada Wujud Malaikat - Ali Akbar; Muhammad Maqsum Lubis; Ardiansyah; Alfan Yurion (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study is motivated by the importance of understanding faith in angels as a pillar of Islamic belief, which isoften accepted normatively without comprehensive exegetical analysis. This research aims to examine Qur'anic verses concerning the existence of angels and analyze interpretations from classical and contemporary scholars. The study employs a qualitative approach with a library research method, drawing on tafsir works from scholars such as Ibn Kathir, Al-Tabari, and Quraish Shihab. The findings indicate that angels are unseen beings with distinct characteristics, including having wings, the ability to transform into different forms, being genderless, and existing in vast numbers. Interpretations among scholars vary, ranging from textual to rational approaches, particularly regarding the essence of angels. In conclusion, belief in angels is not merely theological but also carries practical implications, such as fostering honesty, obedience, and moral awareness. This study highlights the need for a contextual understanding of angels to maintain relevance in contemporary life.